Public servants coping with competing demands on their agency in client relationships. Issue 5 (12th June 2020) - Tuominen, Tiina; Hasu, Mervi
Abstract : Purpose: This paper analyzes how public servants who work with young people discursively cope with competing demands on their agency, defined as their orientation toward and capabilities to influence their clients. Previous studies revealed how public servants treat their clients when facing competing demands but paid less attention to how public servants define their agency. Design/methodology/approach: Micro-level discourse analysis is applied to analyze how public servants represent their agency in client relationships, drawing on interviews with nine individuals in a Finnish city who work with young people lacking jobs or school placements. Findings: Instead of describing their agency coherently, the interviewees applied several discourses to represent their agency differently in relation to different demands. This ability to navigate contradictory discourses is discussed as reflexive discursive coping strategy, which enables public servants to maintain a positive image of their agency despite tensions at work. Research limitations/implications: Although the method does not allow direct generalizations, it reveals discursive strategies likely to be found in many contemporary public organizations. Practical implications: The study indicates a need to better acknowledge and nurture the multifaceted nature of agency to improve service quality. Originality/value: The findings deepen the view on tensions in public servants' work and show that diverse discourses not only create anxiety but also help individuals dealing with contradictory work.